Modeling of Service Supply Chain and Its Relationship on Repurchase Intention: Case study of Lion Air’s in Indonesia - Rivai, Prabumenang Agung Kresnamurti; Afpriyanto, Ari; Rizan, Mohamad; Omar, Khatijah (International Journal of Supply Chain Management, 2020)
Abstract— Over the past decade, the air travel passengers in Indonesia was recorded high and increased time to time. However, besides the big opportunities, the air travel providers have faced numerous issues such as airlines operation. In conjunction with the issue, this study aims to investigate the model of service supply chain and its relationship on repurchase intention in Lion Airlines. The design of this study is quantitative approach through survey questionnaire. A total of 200 passengers have participated in this study and the data analyzed using structural equation modeling that assisted by LISREL-8. The results of analysis show that Service supply chain and Complaint Handling have a significant and positive relationship on Corporate Image. Also, this study found that Delay has negatively and significant effect on Repurchase Intention. Service supply chain, Complaint Handling and Corporate Image have a significant positive relationship on Repurchase Intention. In conclusion, this study suggests the airlines must improve their strategies to provide the best service to passengers. It aims to increase their repurchase intention for Lion Airlines.Keywords— Service supply chain, Delay, Complaint Handling, Corporate Image, Repurchase Intention.